Penerapan protokol kesehatan di masa pandemi Covid-19 pada keluarga yang mengunjungi pasien rawat inap - Ana Astuti; Lolita Sary; Nurul Aryastuti (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: Coronavirus are a group of viruses that can cause disease in animals or humans. From the observations of inpatient family visitors on December 20, 2020 from 30 respondents, it was found that 83% of visitors used masks, 53% of visitors washed their hands with soap and 67% of visitors kept their distance.Purpose: To determine the factors related to the application of health protocols during the Covid-19 pandemic.Method: Quantitative study, the design used is analytic with a cross-sectional approach. The population in this study were all families of inpatients in May–June 2021 with a sample was 196 respondents. Bivariate analysis using chi-square and multivariate analysis using linear regression.Results: The univariate study showed that the most moderate compliance was 96 respondents (49%), good knowledge was 120 respondents (61.2%), positive attitude was 106 respondents (54.1%), the positive perception was 107 respondents (54.7%), positive values as many as 104 respondents (53.1%), positive information sources 109 respondents (55.6). The results of the bivariate test showed that there was a relationship between knowledge, attitudes, perceptions, values, and sources of information (p=0.033; 0.017; 0.001; 0.028; 0.006) on compliance with the application of health protocols in inpatient families. The results of the multivariate test showed that perception was the dominant variable (B=0,162) in compliance with the application of health protocols in the families of inpatientsConclusion: The perception variabel has the greatest influence on compliance with the application of health protocols at the Batin Mangunang Tanggamus Hospital in 2021Keywords: Families visiting inpatients; Health Protocol; Pandemic; Covid-19Pendahuluan: Coronavirus merupakan kelompok virus yang dapat menyebabkan penyakit pada hewan atau manusia. Dari hasil observasi pengunjung keluarga pasien rawat inap pada tanggal 20 Desember 2020 dari 30 responden, didapatkan 83% pengunjung menggunakan masker, 53% pengunjung mencuci tangan dengan sabun dan didapatkan 67% pengunjung menjaga jarak.Tujuan: Untuk mengetahui faktor-faktor yang terkait dengan penerapan protokol kesehatan selama pandemi Covid-19.Metode: Desain penelitian yang digunakan adalah analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh keluarga pasien rawat inap pada bulan Mei – Juni 2021 dengan sasaran 344 keluarga pasien rawat inap dengan 196 responden. Analisa bivariat menggunakan Chi-square dan Analisa multivariate menggunakan regresi linier.Hasil: Didapatkan kepatuhan protokol kesehatan dalam kategori sedang sebanyak 96 responden (49%), pengetahuan baik sebanyak 120 responden (61,2%), sikap positif sebanyak 106 responden (54,1%), persepsi positif sebanyak 107 responden (54,7%), nilai-nilai positif sebanyak104 responden (53,1%), sumber informasi positif sebanyak 109 responden (55,6). Hasil uji bivariat didapatkan ada hubungan antara pengetahuan, sikap, persepsi, nilai-nilai, dan sumber informasi (p=0,033; 0,017; 0,001; 0,028; 0,006) terhadap kepatuhan penerapan protokol kesehatan pada keluarga pasien rawat inap. Hasil uji multivariate didapatkan persepsi merupakan variabel dominan (B=0,162) berhubungan dengan kepatuhan penerapan protokol kesehatan pada keluarga pasien rawat inap.Simpulan: Variabel persepsi memiliki pengaruh paling besar terhadap kepatuhan penerapan protokol kesehatan di RSUD Batin Mangunang Tanggamus tahun 2021.